0193 Distributive Interactive Simulation (dis) For Intramedullary Femoral Nailing: A Feasability Study. (1st November 2014) - Sugand, Kapil; Akhtar, Kash; Anand, Amarjit; Patel, Akash; Bhattacharya, Rajarshi; Gupte, Chinmay
Abstract : Background: The worldwide incidence of trauma is increasing and the World Health Organisation has identified it as a major cause of clinical burden globally. Intramedullary nailing is a common orthopaedic procedure and is one of the definitive surgical treatments for open fractures of the lower limb. We piloted the first intraoperative intramedullary nailing scenario and to create a global rating scale for its assessment. Methodology: 9 participants from different stages of orthopaedic training were recruited and attended a lecture showing all the steps required to perform the procedure. The scenario consisted of an Orthopaedic trainee being called into theatre to complete a trochanteric intramedullary nail with the help of a scrub nurse, runner and anaesthetist. Metrics were assessed for each participant by two senior orthopaedic trainees using a novel 16-point global rating score (range 1–5) for which the Cronbach alpha for inter-rater validity was calculated. Each participant was also individually debriefed after the exercise with their assessor for reflection and constructive feedback. Results: 66% of participants were male (n = 6). The median level of training was post-graduate year 4 (range PG yrs 2–7), with experience of observing 10 cases, assisting in 10 cases and none had performed cases independently. Pre-and post-questionnaire results were both significant within the cohort (p = 0.013 and p < 0.0001 respectively). All questions had a positive change in perception. Cronbach alpha was 0.89 of the global rating score with a median score of 62 (77.5%) out of 80. Conclusions: This is the first pilot study to validate an entire simulated intramedullary trochanteric nail under pressure within a multi-disciplinary team environment using a mobile theatre set up. The simulation scenario was found to have significant acceptability and a realistic global rating scale. This simulation scenario can also be reproducible anywhere since it is an out-of-box mobile operating theatre unit. References: Ericsson KA. Deliberate practice and the acquisition and maintenance of expert performance in medicine and related domains. Acad Med 2004;79(10 Suppl):S70–81 Issenberg SB, McGaghie WC, Petrusa ER, et al . Features and uses of high-fidelity medical simulations that lead to effective learning: a BEME systematic review. Med Teach 2005;27(1):10–28 McGaghie WC, Issenberg SB, Cohen ER, Barsuk JH, Wayne DB. Does simulation-based medical education with deliberate practice yield better results than traditional clinical education? A meta-analytic comparative review of the evidence. Acad Med 2011;86:706–11 Reznick RK, MacRae H. Teaching surgical skills-changes in the wind. N Engl J Med 2006;21;355:2664–9